BATIK MOTIF OF PANDAWA FIGURES AS INSPIRATION FOR GLOW IN THE DARK MODERN KEBAYA - Agustina, Sari; Rudianto, M (Institut Seni Indonesia Surakarta, 2024)
In globalization and the current developments, many local fashions have been neglected, one of which is batik. Younger generations are often prefer to wear fashion that is influenced by foreign trends. The clothes used have their own uniqueness according to what the wearer likes. However, in recent years, clothing has often been misunderstood, that clothing is the main cause of harassment of women. In fact, there is no connection between the clothes worn by women and sexual harassment. To dispel rumors circulating that clothing is the cause of harassment, a modern kebaya with pandawa figure motifs with glow in the dark batik is made. Through this clothing, author wished that it can make people think that clothing is not the cause of sexual harassment and hope that it will be able to make women more courageous in dealing with people who behave certain ways.